Africa rise and shine : how a Nigerian entrepreneur from humble beginnings grew a business to $16 billion - Ovia, Jim (Charleston, South Carolina : Forbes Books, 2018)
The road to success is rarely linear and never easy. Despite countless setbacks, Jim Ovia, founder of Zenith Bank, was able to achieve the unthinkable. Africa Rise and Shine is the story of Ovia's business and banking success and how he was able to create one of Africa's largest banks. Spanning decades of both world and Nigerian history, Africa Rise and Shine dives deep into the events that led to Ovia's triumph. Drawing upon his educational experiences and relentless determination, Ovia was able to overcome every hurdle that stood in the way of his bank becoming the national icon that it is today. Africa Rise and Shine outlines the tough, yet necessary business decisions that were essential to Zenith's prolonged success and is filled with valuable takeaways for every businessperson. Learn from one of the best in banking what it takes to truly be successful.
Includes bibliographical references (pages 217-224) and index.
usc 02/11/2022
Keywords: Ovia, Jim; Entrepreneurship; Success in business; BUSINESS & ECONOMICS / Banks & Banking; BUSINESS & ECONOMICS / Entrepreneurship; BUSINESS & ECONOMICS / Leadership; Africa